An interdisciplinary approach for developing novel methods to study silks - Oh, YJ (2021)
Silks remain objects of eternal fascination to mankind; their remarkable material properties and visual lustre attracting decades of commercial and research attention. Though much research has been conducted in the past to attempt to understand the structure of silks – as well as the highly intricate protein dynamics that occur during the spinning process – many gaps in our knowledge remain. Silks are unique in that order and hierarchy exist right from the molecular scale (primary structure of silk proteins), through to the nanoscale (secondary and tertiary silk protein structures), and right up to the microscale (microscale solid fibre). Therefore, an interdisciplinary approach must be used to understand the many facets of silk. In my thesis, I combine chemical and spectroscopic techniques, material testing techniques, and couple them with a core understanding of evolution and biology in an attempt to understand the structure-protein dynamic-mechanical property relationships of silk. I utilise unnatural amino acid incorporation to endow silks with probes for further structural and dynamic studies. I also use various fluorescence microscopy techniques to study silk structure, using silks’ natural fluorescent motifs as well as incorporated fluorophores as contrast agents. Finally, I offer a perspective piece on the highly contentious subject of nanoparticle incorporation in silks as I believe that it is important to validate various claims floating about as they are likely to guide the way for future studies, and they also have important implications in understanding how nanoparticles travel through the bodies of organisms.